Section on Neonatal-Perinatal Medicine 2017
DOI: 10.1542/peds.140.1_meetingabstract.73
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the Urea Cycle Enzyme Genes Are Associated with Persistent Pulmonary Hypertension of Newborn

Abstract: Background-Persistent pulmonary hypertension of the newborn (PPHN) is characterized by elevated pulmonary vascular resistance (PVR). Endogenous nitric oxide is critical for regulation of PVR . Nitric oxide is generated from L -arginine, supplied by the urea cycle (UC). We hypothesized that polymorphisms in UC enzyme genes and low concentrations of UC intermediates are associated with PPHN.Methods-Family based candidate gene analysis to study 48 single nucleotide polymorphisms in 6 UC enzyme genes. Genotyping w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…These differences are potentially due to different patient populations: While Montogmery et al studied preterm infants with BPD, Pearson et al, as well as the current study included term and nearterm infants with PPHN. Finally, Kaluarachchi et al 15 found trends toward lower arginine and citrulline levels in infants with PPHN, though these did not reach statistical significance. These are all relatively small case-control studies (up to 32 cases), and none adjusted for other metabolites.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…These differences are potentially due to different patient populations: While Montogmery et al studied preterm infants with BPD, Pearson et al, as well as the current study included term and nearterm infants with PPHN. Finally, Kaluarachchi et al 15 found trends toward lower arginine and citrulline levels in infants with PPHN, though these did not reach statistical significance. These are all relatively small case-control studies (up to 32 cases), and none adjusted for other metabolites.…”
Section: Discussionmentioning
confidence: 91%
“…Several prior studies suggest a link between PPHN and metabolism via the urea cycle; 12,15 endothelial cells generate the strong pulmonary vasodilator, nitric oxide (NO), from the precursor amino acid, L-arginine, supplied by the urea cycle (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations